2001
DOI: 10.1002/path.953
|View full text |Cite
|
Sign up to set email alerts
|

Expression of angiogenesis‐related molecules in plexiform lesions in severe pulmonary hypertension: evidence for a process of disordered angiogenesis

Abstract: Pulmonary arteries of patients with severe pulmonary hypertension (SPH) presenting in an idiopathic form (primary PH-PPH) or associated with congenital heart malformations or collagen vascular diseases show plexiform lesions. It is postulated that in lungs with SPH, endothelial cells in plexiform lesions express genes encoding for proteins involved in angiogenesis, in particular, vascular endothelial growth factor (VEGF) and those involved in VEGF receptor-2 (VEGFR-2) signalling. On immunohistochemistry and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
266
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(289 citation statements)
references
References 41 publications
(48 reference statements)
11
266
0
3
Order By: Relevance
“…While our data establish that HIF-2␣ is the critical HIF-␣ homolog regulating pulmonary vascular responses, increased HIF-1␣ expression has been observed in PA-derived medial smooth muscle cells and within human plexiform lesions, a morphological hallmark of idiopathic pulmonary arterial hypertension (IPAH), suggesting that HIF1-dependent signaling may contribute to IPAH-associated proliferative vasculopathy (44). In mice, global heterozygous Hif1a deficiency dampened pulmonary vascular responses induced by prolonged hypoxia, a finding that suggested a role for HIF-1 in the pathogenesis of hypoxia-induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…While our data establish that HIF-2␣ is the critical HIF-␣ homolog regulating pulmonary vascular responses, increased HIF-1␣ expression has been observed in PA-derived medial smooth muscle cells and within human plexiform lesions, a morphological hallmark of idiopathic pulmonary arterial hypertension (IPAH), suggesting that HIF1-dependent signaling may contribute to IPAH-associated proliferative vasculopathy (44). In mice, global heterozygous Hif1a deficiency dampened pulmonary vascular responses induced by prolonged hypoxia, a finding that suggested a role for HIF-1 in the pathogenesis of hypoxia-induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Production of VEGF and its receptors is upregulated in human pulmonary tissue in both acute and chronic hypoxia [159]. Increased VEGF expression has also been observed in PAH, accompanied by elevated levels of VEGFR-1 in the affected pulmonary endothelium and specifically elevated levels of VEGFR-2 in plexiform lesions [6,160]; however, other signaling molecules that are typically involved in the VEGF angiogenic signaling cascade appear to decrease: phosphoinositide-3-kinase, Akt, and Src. As a result, a dysregulated response to VEGF has been proposed to critically influence endothelial cell survival, proliferation, and apoptosis.…”
Section: Vascular Effectorsmentioning
confidence: 99%
“…Tuder et al [40] demonstrated immunohistochemically and via in situ hybridization that the EC in the plexiform lesions, not in the normal vasculature, express mRNA and protein for VEGF (the survival factor for EC) and VEGFR-2, thus suggesting that the formation of these lesions in PAH involves a process of disordered angiogenesis. Moreover, in PAH, the population of lung EC expands in a monoclonal pattern [41], and these EC contain an inactivating mutation of the transforming growth factor receptor II [42].…”
Section: The Su5416 Model and Classical Rodent Models Of Pahmentioning
confidence: 99%